2017
DOI: 10.1242/dev.152231
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall-localized atypical β-1,3 glucanase ZERZAUST controls tissue morphogenesis in Arabidopsis thaliana

Abstract: Orchestration of cellular behavior in plant organogenesis requires integration of intercellular communication and cell wall dynamics. The underlying signaling mechanisms are poorly understood. Tissue morphogenesis in Arabidopsis depends on the receptor-like kinase STRUBBELIG. Mutations in ZERZAUST were previously shown to result in a strubbelig-like mutant phenotype. Here, we report on the molecular identification and functional characterization of ZERZAUST. We show that ZERZAUST encodes a putative GPIanchored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…BC1 was also shown to be PI-PLD sensitive. Similarly, the GAP ZERZAUST (ZET) localized not to PM but to the cell wall (Vaddepalli et al 2017).…”
Section: Cell Wall Versus Pm Localizationmentioning
confidence: 99%
“…BC1 was also shown to be PI-PLD sensitive. Similarly, the GAP ZERZAUST (ZET) localized not to PM but to the cell wall (Vaddepalli et al 2017).…”
Section: Cell Wall Versus Pm Localizationmentioning
confidence: 99%
“…For example, whole-genome transcriptomics analysis revealed that many genes responsive to SUB -mediated signal transduction relate to cell wall remodeling [45]. Moreover, Fourier-transform infrared spectroscopy (FTIR)-analysis indicated that flowers of sub and qky mutants share overlapping defects in cell wall biochemistry [46]. Thus, apart from functionally connecting RK-mediated signal transduction and PD-dependent cell-cell communication SUB signaling also relates to cell wall biology.…”
Section: Introductionmentioning
confidence: 99%
“…In Ler background, zet-1 carrying a loss-of-function mutation in ZET locus (At1g64760) (Fig. 1A,B), shows a strong slm mutant phenotype (Vaddepalli et al . 2017) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1J). This construct was used in a previous study to complement zet-1 mutants in L er background (Vaddepalli et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation